Engaging stakeholders to strengthen the local actions for stunting prevention and control in Lombok Barat - Mei Neni Sitaresmi; Tony Arjuna; Siti Helmyati; Budi Santosa; Supriyati Supriyati (Journal of Community Empowerment for Health, 2023)
The determinants of stunting are complex and multisectoral. It is essential and challenging to increase stakeholders’ engagement of the relevant multisector partners in stunting prevention and control. This article aimed to describe the stakeholders’ engagement process in the stunting prevention and control programs in Lombok Barat, Indonesia. This descriptive study was conducted with multisector stakeholders as the study population in Lombok Barat District, Indonesia from August – Desember 2022. Data were collected through observations and documents. Data analysis was done descriptively. This study showed that stakeholders’ engagement is a continuous activity to raise their awareness concerning the stunting issues and encourage them to be actively involved in the programs. Needs assessment and internal planning development, lobbying and advocacy, raising leader commitment, development planning and strategies, and capacity building were accomplished in this study to engage related stakeholders in the stunting interventions in Lombok Barat. The stakeholders who should be involved in the programs are not limited to the stakeholders from the health sector, but must include inter-sectoral stakeholders due to the complexity of the stunting determinants. Moreover, it is necessary to develop key messages to increase the stakeholders’ engagement according to their own needs. Additionally, leadership, leaders’ awareness of health issues as well as their commitment were identified as the main social capital for community action in the stunting prevention and control efforts.